Pengaruh Content Marketing dan e-WOM terhadap Purchase Intention Pada Media Sosial TikTok - Fairuz Naufaliza Salsabila; Baroroh Lestari (Jurnal Ekonomi dan Bisnis Digital, 2024)
The advancement of social media has had a positive impact by expanding the space for interaction, with TikTok being one of the key platforms. TikTok is a social media platform that offers various interesting effects that are easy to use by all users. TikTok also supports content marketing and electronic word of mouth strategies to influence purchase intention. This study aimed to examine the effect of content marketing and electronic word of mouth partially and simultaneously on purchase intention. This study used an explanatory research method with a quantitative approach, utilizing a questionnaire for data collection from followers of the TikTok account @larissamalangofficial, with a purposive sampling technique. The data analyses in this study used classic assumption tests and multiple linear regression analysis. The results of partial hypothesis testing, content marketing had a positive but insignificant effect on purchase intention, while electronic word of mouth had a positive and significant effect on purchase intention. The results of simultaneous hypothesis testing showed that content marketing and electronic word of mouth had a positive and significant effect on purchase intention. Keywords: Content Marketing, e-WOM, Purchase Intention